The Influence Of Work Environment And Work Motivation On Employee Performance At The Regional Finance Agency (BKD) Office Of Seluma Regency - Fitrah, Muhammad Idza Al; Susanti, Neri; Fitriano, Yun (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Human Resource Management (HRM) is a strategic area in an organization. So, in realizing the goals, objectives, vision, and mission of the organization, strategic planning is needed for the development and management of its organization in the Regional Finance Agency in Seluma Regency Government. The purpose of this study is the effect of work environment and work motivation on employee performance at the Regional Finance Agency (BKD) office of Seluma Regency. This type of research is a type of quantitative research. The data collection method in this study used a questionnaire technique, with a sample of 63 respondents. The results showed that multiple linear regression Y = 20,822 + 0.150 X1 + 0.233 X2 +3.272. Where the coefficient is positive, it means that there is a positive or unidirectional relationship between the work environment variable (X1) and work motivation, on employee performance at the Regional Finance Agency Office of Seluma Regency. The results show that the results of the work environment test (XI) show t count 3.398>t table 1.999 and signification 0.001<0.05, then the results of the hypothesis Ha is accepted and Ho is rejected, meaning that the work environment (XI) has a positive and significant effect on employee performance. The results of the work motivation test (X2) show t count 7.507>t table 1.999 and signification 0.000 <0.05, then the results of the Ha hypothesis are accepted and Ho is rejected, meaning that work motivation (X2) has a positive and significant effect on employee performance at the Regional Finance Agency Office of Seluma Regency. The results of the comparison value of F count with F table, the value of F count is greater than F table, namely 32,981>2.76, it is concluded that Accepting the Hypothesis, meaning that there is a simultaneous influence between the work environment (XI) and work motivation (X2) on employee performance (Y) at the Regional Finance Agency Office of Seluma Regency. This can be seen at a significance level of 0.000 <0.05